2019
DOI: 10.1021/acsnano.9b00008
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of a Polypeptide with a Protein Nanopore Under Crowding Conditions

Abstract: Molecular crowding, a ubiquitous feature of the cellular environment, has significant implications in the kinetics and equilibrium of biopolymer interactions. In this study, a single charged polypeptide is exposed to competing forces that drive it into a transmembrane protein pore versus forces that pull it outside. Using single-molecule electrophysiology, we provide compelling experimental evidence that the kinetic details of the polypeptide-pore interactions are substantially affected by high concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 70 publications
4
65
0
Order By: Relevance
“…Notably, PEG 8000 had a weaker effect on Syn B2:haemolysin association than PEG 6000, which could not solely be explained by the excluded volume. Instead, the observed size dependence was related to the osmotic pressure arising from the small and large crowders, in agreement with the theoretical predictions [166,167], although also different effects of PEGs on diffusion and compaction state of Syn B2 peptide could play a role.…”
Section: Crowding‐mediated Transport Through Biological Membranessupporting
confidence: 88%
See 1 more Smart Citation
“…Notably, PEG 8000 had a weaker effect on Syn B2:haemolysin association than PEG 6000, which could not solely be explained by the excluded volume. Instead, the observed size dependence was related to the osmotic pressure arising from the small and large crowders, in agreement with the theoretical predictions [166,167], although also different effects of PEGs on diffusion and compaction state of Syn B2 peptide could play a role.…”
Section: Crowding‐mediated Transport Through Biological Membranessupporting
confidence: 88%
“…However, specific attractive interactions with crowders may have a dominant effect on the direction of the transport [165]. Most recently, protein transport through a membrane-embedded a-haemolysin nanopore with a crowded solution phase was studied experimentally [167]. Haemolysin, a pore-forming bacterial toxin, has extensive use in nanotechnology applications where its wide transmembrane channel allows translocation of synthetic and biopolymers, such as DNA strands and polypeptide chains [168].…”
Section: Polymer Translocation Under Crowded Conditionsmentioning
confidence: 99%
“… 53 In 2019, Larimi et al investigated the effect of crowding on the interactions of a polypeptide with a biological nanopore, concluding that crowded conditions resulted in a stronger polypeptide–nanopore interaction. 54 The enhancement of the capture rate of DNA in biological nanopores by crowding 51 could be associated with the disruption of electroosmotic flow in the nanopore. Indeed, Yusko et al demonstrated that the formation of the asymmetric concentration gradient by the addition of various percentages of dimethyl sulfoxide (DMSO) into the electrolyte altered the solution properties as well as the electroosmotic flow in a conical nanopore.…”
mentioning
confidence: 99%
“…This definition of the partition coefficient normalizes out the pore volume, which means that  is a measure of the lifetime of a polymer in the pore compared to a polymer in a pore-sized volume in bulk solution. This convention leads to a partition coefficient greater than 1 and thus a free energy of polymer occupation in the pore greater than the bulk, as used previously by others (36,37). In addition, we note that all analysis throughout is performed at a single applied potential (70 mV) and each free energy value is to be interpreted as corresponding to that applied potential (i.e., G 0 total = G 0 total at 70 mV).…”
Section: Theoretical Backgroundmentioning
confidence: 98%